Tolerance Threshold and Phyto-assessment of Cadmium and Lead in Vetiver Grass, Vetiveria zizanioides (Linn.) Nash - Chuck Chuan Ng (Science Faculty of Chiang Mai University, 2019)
Various types of plant species have been extensively used for heavy metals phyto-remediation without taking into consideration its tolerance threshold. In this study, Vetiver grass, Vetiveria zizanioides (Linn.) Nash was evaluated under five different sets of contaminated spiked cadmium (5Cd, 10Cd, 50Cd, 100Cd and 150Cd mg/kg) and lead (50Pb, 100Pb, 200Pb, 400Pb and 800Pb mg/kg) concentration levels in soil. The growth performance, metal tolerance and phyto-assessment of Cd and Pb in the roots and tillers were assessed using flame atomic absorption spectrometry (FAAS). Tolerance index (TI), translocation factor (TF), biological transfer factor (BTF), biological accumulation coefficient (BAC) and metal uptake efficacy were used to determine the Cd and Pb translocation capability in Vetiver grass. Significantly higher (p<0.05) accumulation of Cd and Pb was recorded in the roots of all spiked treatments. Furthermore, strong and significantly positive correlations were exhibited between the increased levels of spiked heavy metal concentrations with both Cd (r=0.975) and Pb (r=0.952) accumulations. The results of this study showed Vetiver grass as an effective phyto-stabilizer for both Cd and Pb. Nevertheless, the growth of Vetiver grass was restricted when the tolerance threshold of 100 mg/kg (dry weight basis) Cd was exceeded in the contaminated soil.